Clinical relevance of sperm morphology assessment using strict criteria and relationship with sperm-mucus interaction in vivo and in vitro* - Eggert-Kruse, Waltraud; Reimann-Andersen, Jutta; Rohr, Gerhard; Pohl, Sabine; Tilgen, Wolfgang; Runnebaum, Benno (Fertility and sterility, 1995)
Objective - To determine the relationship of the differentiated morphological pattern of semen samples according to strict criteria and sperm-mucus interaction in vivo and in vitro. - Patients - One hundred sixty-three randomly chosen couples with long-standing infertility (median duration of infertility 4 years, range 1 to 19 years). - Setting - Outpatient clinic of the fertility unit at the Women’s University Hospital of the University of Heidelberg, Heidelberg, Germany. - Main Outcome Measures - Sperm morphology assessment using strict criteria (Tygerberg or Norfolk classification) parallel to standard methods of sperm analysis: Evaluation of the cervical factor of patients’ female partners, including a microbial screening of genital secretions of both partners; Examination of sperm migration ability in vivo under hormonally controlled conditions for the cervical mucus (CM) quality and in vitro with the crossed sperm-CM penetration test performed with CM of patients’ partners, as well as with CM and spermatozoa of donors; Determination of the selection capacity of CM with regard to sperm morphology by means of a biological model; Prospective analysis of the differentiated morphological pattern with respect to couples’ subsequent fertility within 6 months. - Results - Using stict criteria, amorphous sperm heads were the most frequently found sperm anomaly (severely amorphous forms: median, 28%; range, 4% to 62%). The morphology index offered a median of 45% (range, 7% to 80%). Results correlated significantly with routine sperm analysis, including standard morphology. The morphological pattern differed significantly in samples offering adequate or inadequate ability to penetrate CM in the standardized sperm-CM penetration test or in the postcoital test, with the percent of severely amorphous heads as the most important parameter. Neck and tail defects did not play an important role. During passage of mucus columns in vitro, the rate of pathological spermatozoal forms was reduced significantly, from a median of 65% to a median of 38%. Better functional capacity of spermatozoa with normal head morphology also was reflected by a significantly higher pregnancy rate under natural conditions of conception. - Conclusions - Sperm morphological properties, determined with strict criteria, are important factors for sperm ability to penetrate the mucus barrier at the uterine cervix before reaching the site of fertilization, but sperm morphology is only one among other parameters determining the complex phenomenon of sperm-mucus interaction.
Elektronische Reproduktion der Druck-Ausgabe 25. April 2016
Gesehen am 21.11.2024